Artificial intelligence planning and 3D printing augmented modules in the treatment of a complicated hip joint revision: a case report - Liu, Yikai; Zhang, Zian; Wang, Wenzhe; Yu, Chaoqun; Liu, Chang; Huang, Zhenchao; Xu, Kaige; Zhang, Haining (Frontiers in Surgery, 2023)
Total hip revision with osseous defectdefects can be very difficult. Artificial intelligence offers preoperative planning, real-time measurement, and intraoperative judgment, which can guide prothesis placement more accurately. Three-dimensional printed metel augment modules which are made according to the individualized osseous anatomy, can fit the osseous defectdefects well and provide mechanical support. In this case, we used AI to plan the size and position of the acetabular cup and 3D-printed augmented modules in a complicated hip revision with an acetabular bone defectdefects, which achieved stable fixation and relieved hip pain postoperatively.